Ethnic, racial and regional inequalities in access to COVID-19 vaccine, testing and hospitalization: Implications for eradication of the pandemic - Ahlberg, Beth Maina; Bradby, Hannah (Frontiers in Sociology, 2022)
The corona pandemic has made visibile the face of global inequalities as exemplified by failed global access to sufficient vaccine doses and the disastrous effects of inequalities across geopolitical boundaries. This is to say that the COVID-19 pandemic has forced us to comprehend the entrenched inequalities within and between countries and global regions. While many countries in the global north have acquired more vaccines than they need, many countries in the global south still have very limited access. Moreover, it is expected that countries in the global north are likely to vaccinate their whole populations by the end of 2021, but those in the global south may not even complete vaccinating 70% of their population for so-called herd immunity by 2024. This paper aims to explore the socio-economic and political structural factors that have created the disparities in access to vaccines and that seem set to maintain the inequalities. We sketch the role that neoliberal developments have had in deregulating and financializing the system that funds the development and distribution of vaccine, and how this contributes to maintaining and widening global disparities in vaccine access.